Educational robotics as a pedagogical resource for K-12 students with learning difficulties - da Silva, Maria da Guia Torres; Araújo Maia, Claudia Juliete do Nascimento; Fernandes Curvelo, Carla da Costa; Garcia, Luciane Terra dos Santos; Gonçalves, Luiz Marcos Garcia (Scientific reports, 2025)
Learning difficulties in children can have a variety of causes, often interconnected. Factors such as emotional problems (anxiety, stress), communication difficulties, inadequate teaching methodologies, health problems, lack of family support, and even genetic and prenatal factors can contribute to these difficulties. There are several ways to tackle the problem, mainly the use of active methodologies involving technology tools is one of them. In this direction, to help alleviate these problems, this article analyzes the possible use of educational robotics as a support tool to help children with learning difficulties in the teaching-learning process. We seek to answer our main research question, which is to identify if and how educational robotics can help the development of these students’ skills and abilities. To do that, we first conducted a systematic review of the literature on the subject, from which we performed an in-depth analysis, including several issues, not just those related to learning difficulties. From this initial stage, we found that there are few studies that address this topic and several open questions. The main gap observed is that many students with learning difficulties are present in schools, but most of them do not participate in robotic activities. Also, in some cases, they show no interest, as will be discussed, on the basis of strictly related works. Given the novelty of the subject and the existence of gaps, we conducted an investigation using a qualitative–quantitative research methodology, using a questionnaire as a data collection tool. The analysis of the results indicates an increase in the use of robotics in education for students with learning difficulties and, above all, that these students benefit from its use. Thus, this study contributes with a step forward in demonstrating that Educational Robotics can help students with learning difficulties.